Examination of Turkish curriculums of the republic period in terms of objectives - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
The aim of this study is to examination of the Turkish primary school curriculums of the republican era in terms of objectives. The data required for this study, which is an exemplary of qualitative research, have been collected by means of document review, the objectives of the Turkish curriculums of primary schools have been subjected to an in-depth analysis and the changes that have been made have been put forward. When examined in general, it has been determined that the objectives specified in the Turkish curriculums of the primary schools have been deepened in terms of both quality and quantity throughout the years. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: curriculum; Turkish curriculum; objective